Effect of strain rate on hydrogen embrittlement susceptibility of twinning-induced plasticity steel pre-charged with high-pressure hydrogen gas. (14th September 2016) - Bal, B.; Koyama, M.; Gerstein, G.; Maier, H.J.; Tsuzaki, K.
Abstract: The effects of tensile strain rate on the hydrogen-induced mechanical and microstructural features of a twinning-induced plasticity (TWIP) steel were investigated using a Fe-23Mn-0.5C steel with a saturated amount of hydrogen. To obtain a homogeneous hydrogen distribution, high-pressure hydrogen gas pre-charging was performed at 423 K. Similar to previous studies on hydrogen embrittlement, the deterioration in the tensile properties became distinct when the strain rate was decreased from 0.6 × 10 −3 to 0.6 × 10 −4 s −1 . In terms of microstructural features, hydrogen-precharging decreased the thickness of deformation twin plates, and it localized dislocation slip. Moreover, facets of the hydrogen-induced quasi-cleavage feature on the fracture surface became smoother with decreasing strain rate. In this study, we proposed that a combined effect of hydrogen segregation, slip localization, and thinning of twin plates causes the hydrogen embrittlement of TWIP steels, particularly at a low strain rate. Highlights: Hydrogen embrittlement is substantially more pronounced at low strain rates. Introduction of hydrogen decreases the average twin thickness. Hydrogen enhances the microstructural activities. Hydrogen charging changes the fracture mode from ductile to quasi-cleavage. Strain rate dependent hydrogen embrittlement mechanism is proposed.